Association of Response to Inhaled Nitric Oxide and Duration of Mechanical Ventilation in Pediatric Acute Respiratory Distress Syndrome*. Issue 11 (November 2017) - Dowell, Jasmine C.; Thomas, Neal J.; Yehya, Nadir
Abstract : Objectives: Literature regarding appropriate use of inhaled nitric oxide for pediatric acute respiratory distress syndrome is sparse. This study aims to determine if positive response to inhaled nitric oxide is associated with decreased mortality and duration of mechanical ventilation in pediatric acute respiratory distress syndrome. Design: Retrospective cohort study. Setting: Large pediatric academic medical center. Patients or Subjects: One hundred sixty-one children with pediatric acute respiratory distress syndrome and inhaled nitric oxide exposure for greater than or equal to 1 hour within 3 days of pediatric acute respiratory distress syndrome onset. Interventions: Patients with greater than or equal to 20% improvement in oxygenation index or oxygen saturation index by 6 hours after inhaled nitric oxide initiation were classified as "responders." Measurements and Main Results: Oxygenation index, oxygen saturation index, and ventilator settings were evaluated prior to inhaled nitric oxide initiation and 1, 6, 12, and 24 hours following inhaled nitric oxide initiation. Primary outcomes were mortality and duration of mechanical ventilation. Baseline characteristics, including severity of illness, were similar between responders and nonresponders. Univariate analysis showed no difference in mortality between responders and nonresponders (21% vs 21%; p = 0.999). Ventilator days were significantly lower in responders (10 vs 16; p < 0.001). Competing risk regression (competing risk of death) confirmed association between inhaled nitric oxide response and successful extubation (subdistribution hazard ratio = 2.11; 95% CI, 1.41–3.17; p < 0.001). Response to inhaled nitric oxide was associated with decreased utilization of high-frequency oscillatory ventilation and extracorporeal membrane oxygenation and lower hospital charges (difference in medians of 424, 000). Conclusions: Positive response to inhaled nitric oxide was associated with fewer ventilator days, without change in mortality, potentially via reduced use of high-frequency oscillatory ventilation and extracorporeal membrane oxygenation. Future studies of inhaled nitric oxide for pediatric acute respiratory distress syndrome should stratify based on oxygenation response, given the association with favorable outcomes. Abstract : Supplemental Digital Content is available in the text.